Molecular cloning of the flavin-containing monooxygenase (form II) cDNA from adult human liver. - Lomri, N (1992)
Complementary DNA (cDNA) clones encoding the adult human liver flavin-containing monooxygenase (FMO; dimethylaniline N-oxidase, EC 1.14.13.8) were isolated from lambda gt10 and lambda gt11 libraries. The cDNA libraries were screened with three synthetic 36-mer oligonucleotide probes derived from the nucleic acid sequence of the pig liver FMO cDNA. The deduced amino acid sequence for the adult human liver FMO was quite distinct from the pig liver FMO, and adult human liver FMO was designated form II (HLFMO II). The full-length cDNA sequence of HLFMO II [2119 base pairs (bp)] had an open reading frame of 1599 nucleotides, which encoded a 533-amino acid protein of Mr 59,179, a 5'-noncoding region of 136 nucleotides and a 3'-noncoding region of 369 nucleotides excluding the poly(A) tail. The deduced amino acid sequence of HLFMO II had 80% similarity with the rabbit liver FMO II but only a 52%, 55%, and 53% amino acid similarity with the rabbit liver (form I), the pig liver (form I), and fetal human liver (form I) FMOs, respectively. RNA analysis of adult human liver RNA showed that there was one HLFMO II mRNA species. Analysis of genomic DNA indicated that HLFMO II was the product of a single gene. These results indicated that the deduced amino acid sequence for HLFMO II contained highly conserved residues and suggested that FMO enzymes were closely related and, undoubtedly, derived from the same ancestral gene.